Twelve-year outcomes of bedside laser photocoagulation for severe retinopathy of prematurity - Yang, Bingzhi; Lian, Chaohui; Tian, Ruyin; Chen, Yi; Tang, Song; Xiang, Haishan; He, Honghui; Zhang, Guoming (Frontiers in Pediatrics, 2023)
Purpose: To evaluate the 12-year outcomes of bedside laser photocoagulation (LP) for severe retinopathy of prematurity (ROP) under sedation combined with ocular surface anesthesia in neonatal intensive care units (NICU). Design: Retrospective case series study. Methods: Infants treated with bedside LP for severe ROP from April 2009 to September 2021 were included. All LP treatments were performed under sedation and surface anesthesia at the bedside in NICU. The data were recorded for clinical and demographic characteristics, total laser spots, duration of treatment, proportion of total regression of ROP, proportion of recurred, and adverse events. Results: A total of 364 infants (715 eyes) were included with a mean Gestational age (GA) of 28.6±2.4 weeks (range: 22.6 to 36.6 weeks) and a mean birth weight of 1,156.0±339.0 grams (range: 480 to 2,200 grams). The mean number of laser spots was 832±469 and the mean duration of treatment was 23.5±5.3 minutes per eye. A total of 98.3% eyes responded to LP with complete regression of ROP. ROP recurred in 15 (2.1%) eyes after initial LP. Additional LP was performed in 7 (1.0%) eyes. No patient exhibited mistaken LP of other ocular tissues, and there were no serious ocular adverse effects. None of them needed endotracheal intubation. Conclusions: It is effective and safe to perform a bedside LP treatment for premature infant with severe ROP under sedation and surface anesthesia in NICU, especially for infant whose general condition is unstable, and not suitable for transport.